Cellular senescence in the pathogenesis of pulmonary arterial hypertension: the good, the bad and the uncertain - Safaie Qamsari, Elmira; Stewart, Duncan J. (Frontiers in Immunology, 2024)
Senescence refers to a cellular state marked by irreversible cell cycle arrest and the secretion of pro-inflammatory and tissue-remodeling factors. The senescence associated secretory phenotype (SASP) impacts the tissue microenvironment and provides cues for the immune system to eliminate senescent cells (SCs). Cellular senescence has a dual nature; it can be beneficial during embryonic development, tissue repair, and tumor suppression, but it can also be detrimental in the context of chronic stress, persistent tissue injury, together with an impairment in SC clearance. Recently, the accumulation of SCs has been implicated in the pathogenesis of pulmonary arterial hypertension (PAH), a progressive condition affecting the pre-capillary pulmonary arterial bed. PAH is characterized by endothelial cell (EC) injury, inflammation, and proliferative arterial remodeling, which leads to right heart failure and premature mortality. While vasodilator therapies can improve symptoms, there are currently no approved treatments capable of reversing the obliterative arterial remodeling. Ongoing endothelial injury and dysfunction is central to the development of PAH, perpetuated by hemodynamic perturbation leading to pathological intimal shear stress. The precise role of senescent ECs in PAH remains unclear. Cellular senescence may facilitate endothelial repair, particularly in the early stages of disease. However, in more advanced disease the accumulation of senescent ECs may promote vascular inflammation and occlusive arterial remodeling. In this review, we will examine the evidence that supports a role of endothelial senescence to the pathogenesis of PAH. Furthermore, we will compare and discuss the apparent contradictory outcomes with the use of interventions targeting cellular senescence in the context of experimental models of pulmonary hypertension. Finally, we will attempt to propose a framework for the understanding of the complex interplay between EC injury, senescence, inflammation and arterial remodeling, which can guide further research in this area and the development of effective therapeutic strategies.